Competence profiles updates for the future digital society: a comparative approach - Capogna, Stefania; Greco, Francesca (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The essay illustrates a comparative analysis oriented to understanding the national digital strategies of countries’ partners involved in the Erasmus+ Project RE-EDUCO. Digital transformation in Europe will rapidly accelerate. New technologies play a central role in this process, influencing how people live, interact, study and work. The mismatch between labour supply and demand is among the most recurring complaints that can be read in European and supranational documents that outline the digital society’s developments. The essay examines this mismatch, performed through ETM, applied to the comparative analysis of the reports elaborated by the five partner countries involved in the project. The essay starts with an overview of the issue and methodology adopted to continue with the analysis and discussion data, and some summary conclusions suggested by this work.